2023
DOI: 10.1111/opo.13084
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral choroidal thickness and eye length changes during accommodation

Abstract: Eye length increases during accommodation, both on-axis and in the periphery. The aim of this study was to determine whether the peripheral choroid thins with accommodation and to determine the relationship with eye length changes measured at the same location. Methods: Subjects included 53 young adults in good ocular and general health, with 19 emmetropes and 34 myopes. Measurements from the right eye were made for 0 D and 6 D accommodation stimuli for ±30° horizontal visual field/retinal locations in 10° ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(71 reference statements)
0
1
0
Order By: Relevance
“… 7 9 Additionally, that 3 of the 6 myopes (−0.50 to −1.25 D) and 11 of the 15 significant hyperopes (+2.00 to +3.00D) were uncorrected during the parts of the study limits the generalizability of the results for these refractive error groups. Previous studies have reported that both accommodation 84 and defocus 41 can influence choroidal thickness, potentially affecting the uncorrected hyperopes and the uncorrected myopes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 7 9 Additionally, that 3 of the 6 myopes (−0.50 to −1.25 D) and 11 of the 15 significant hyperopes (+2.00 to +3.00D) were uncorrected during the parts of the study limits the generalizability of the results for these refractive error groups. Previous studies have reported that both accommodation 84 and defocus 41 can influence choroidal thickness, potentially affecting the uncorrected hyperopes and the uncorrected myopes, respectively.…”
Section: Discussionmentioning
confidence: 99%